PENGARUH JUMLAH ASUPAN BISKUIT COKELAT TERHADAP AKUMULASI PLAK GIGI PADA ANAK USIA 9-11 TAHUN (Kajian pada Sekolah Dasar Negeri Bangirejo 1) - , SUKRON TAJUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Biscuit was an appropriate kind of dry snacks which most wanted to be served for the lunch of children to do some activities in school. Carbohydrate, especially sucrose, was a main component of ingredients of biscuit which played role as sweetener. Chocolate was the most used filling for biscuit because of the taste that is loved most by the children. The food debris that was left after consuming biscuit of chocolate had important role in dental plaque formation process. This process can be worst because of the high sticky property of chocolate. This research aimed to know the effect of the amount of consumption of biscuit toward the changes of dental plaque formation on children ages 9-11 years old. Quasi Experimental research on 30 subjects was divided into two groups. Group 1 was given preferential treatment to consume 29.4 gram of biscuit and the group 2 was given favorable treatment to consume 58.8 gram of biscuit. Calculation of dental plaque score carried out two hours after consuming biscuit by using Personal Hygiene Performance Modified (PHP-M) by Martens and Meskin. Dental plaque score data from each group measurements were analyzed with independent t-test. The results showed that the average of dental plaque score after consuming 58.8 gram of biscuit (0,822 Â± 0,152) was greater than after consuming 29.4 gram of biscuit (0,609 Â± 0,084). Independent t-test result showed that there was a significant statistically difference of average of dental plaque score between two groups (t = -6,689